Village-Owned Enterprise E-Government Adoption: A UMEGA Analysis in Tangerang - Aryo Wicaksono; Heri Faturrahman (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines the determinants of behavioral intention among non-adopter BUM Desa managers in utilizing the bumdes.kemendesa.go.id portal for legal entity registration in Tangerang Regency, Indonesia, using the Unified Model of Electronic Government Adoption (UMEGA). Research Methodology: A quantitative cross-sectional survey was conducted on 112 non-adopter BUM Desa managers during May–June 2026. Data were collected via a structured online questionnaire measuring seven UMEGA constructs with 28 indicators on a six-point Likert scale. Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 was employed for analysis. Results: Four of seven hypotheses were supported. Effort Expectancy (? = 0.263, p = 0.013) and Social Influence (? = 0.260, p = 0.046) positively influenced Attitude. Facilitating Conditions significantly affected both Effort Expectancy (? = 0.365, p = 0.007) and Behavioral Intention (? = 0.304, p = 0.044). Performance Expectancy, Perceived Risk, and the Attitude-to-Behavioral Intention path were not significant. Conclusions: In mandatory G2B e-government contexts, adoption intention is driven by perceived simplicity, social pressure, and facilitating resources rather than by functional expectations or attitudinal mediation. The non-significant attitude-intention path is attributed to the mandatory nature of the service, which renders UMEGA's central mediation pathway less operative and calls for contextual recalibration. Limitations: The cross-sectional design, single-regency scope, and modest R² values limit causal inference and generalizability. Contributions: This study extends UMEGA to a mandatory G2B village-level context and recommends that policymakers prioritize operational support and village-head endorsement over attitudinal campaigns.